Honokiol protects against diabetic retinal microvascular injury via sirtuin 3-mediated mitochondrial fusion - Shi, Jiemei; Liu, Min; Zhao, Jiajie; Tan, Ye; Jiang, Chunhui (Frontiers in Pharmacology, 2024)
Mitochondrial dysfunction and oxidative stress play important roles in diabetic retinal vascular injuries. Honokiol (HKL) is a small-molecule polyphenol that exhibits antioxidant effects and has a beneficial effect in diabetes. This study aimed to explore the potential ability of HKL to ameliorate vascular injury in diabetic retinopathy (DR) and its possible mechanisms of action. The effect of HKL was evaluated in vascular injury in an in vivo type 2 diabetic (db/db) mouse model. In vitro, retinal microvascular endothelial cells were treated with high glucose (HG) to simulate the pathological diabetic environment. Cell viability, expression of apoptosis-related proteins, cellular reactive oxygen species, mitochondrial membrane potential, and morphological changes in the mitochondria were examined. The diabetic mice exhibited severe retinal vascular damage, including vascular leakage in vivo and capillary endothelial cell apoptosis in vitro. HKL reversed the retinal vascular leakage in the diabetic mice. In vitro, HKL improved retinal capillary endothelial cell viability, decreased apoptosis, and reversed the HG-induced increased cellular oxidative stress and mitochondrial fragmentation. The sirtuin 3 (SIRT3) inhibitor 3-TYP blocked all the in vivo and in vitro protective effects of HKL against diabetic retinal vascular leakage and capillary endothelium and eliminated the decrease in oxidative stress levels and reduction of mitochondrial fragmentation. In conclusion, these findings suggest that HKL inhibits vascular injury in DR, which was likely achieved through SIRT3-mediated mitochondrial fusion. This study provides a potential new strategy for the treatment of DR.